2022
DOI: 10.21203/rs.3.rs-2100169/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Economic Policy Uncertainty Impact Firms’ Capital Structure Policy? Evidence from Western European Economies

Abstract: This study specifically investigates the impact of economic policy uncertainty (EPU) on the travel and leisure (TL) companies’ debt holdings policy. To do so, the present study selects 92 publicly listed TL companies operating in Western Europe’s top tourist destinations, and performs both the static and dynamic panel data estimation approaches during the 2005–2019 period. The results reveal that the EPU negatively impacts TL firms’ debt holdings, implying that firms tend to decline in debt levels by rising EP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Besides, several studies used TEU as a predictor of equity and cryptocurrency markets at the aggregate level and concluded that Twitter sentiments could predict market returns (Chatterjee & French, 2021). As discussed in previous studies, a high level of uncertainty leads to a rise in the volatility of a firm's cash flows, reducing the firm's capital investment and financial performance, deteriorating financial markets (e.g., a higher cost of external funding and financial shortfalls), and decreasing the prosperity of business environments, which ultimately impacts firms' stock prices (e.g., Athari & Bahreini, 2023;Irani et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
“…Besides, several studies used TEU as a predictor of equity and cryptocurrency markets at the aggregate level and concluded that Twitter sentiments could predict market returns (Chatterjee & French, 2021). As discussed in previous studies, a high level of uncertainty leads to a rise in the volatility of a firm's cash flows, reducing the firm's capital investment and financial performance, deteriorating financial markets (e.g., a higher cost of external funding and financial shortfalls), and decreasing the prosperity of business environments, which ultimately impacts firms' stock prices (e.g., Athari & Bahreini, 2023;Irani et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
“…Firms might adopt a risk-averse approach when confronted with shocks of uncertainty (Vural-Yavaş, 2020). Furthermore, firms may demonstrate financial prudence in reaction to uncertainty, for example, augmenting their cash holdings (Athari & Bahreini, 2023). Consequently, companies could exhibit heightened caution and sagacity in their investment choices, which may translate into enhancing corporate performance.…”
Section: Literature Review and Hypotheses To Be Testedmentioning
confidence: 99%
“…For the third channel, uncertainty can be perceived as a form of risk that enterprises confront, prompting a precautionary motive where they might augment their cash reserves in response to heightened uncertainty (Athari & Bahreini, 2023). High liquidity (cash reserves) can function as a safeguard, enabling corporate managers to forestall default risk (Arnold, 2014).…”
Section: Literature Review and Hypotheses To Be Testedmentioning
confidence: 99%